Implementation of Internal Quality Standards at the Faculty of Economics and Islamic Law, Ahmad Dahlan Islamic University Sinjai - Abdul Rahman Latief; Umar Sulaiman; Yuspiani Yuspiani; Rahmat Gusnadi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study serves as an effort to explore the implementation of the Internal Quality Standards at the Faculty of Economics and Islamic Law, Universitas Islam Ahmad Dahlan, Sinjai Regency. A qualitative approach was employed, with data collected through interviews, observations, and documentation, which were then analyzed using the Miles and Huberman method. The findings indicate that the implementation of the Internal Quality Assurance System (SPMI) has been running effectively, with an average quality achievement exceeding 80%. This success is reflected in the attainment of several key indicators, such as Foreign Language Development, Learning Content, and Research Assessment, which reached 100%. However, some aspects still require improvement, particularly in research quality and alumni management, which have not yet met optimal standards. The active involvement of various stakeholders, including lecturers, students, and alumni, plays a crucial role in the success of this system. To further enhance educational quality, it is recommended to strengthen research support, optimize academic facilities, and reinforce stakeholder engagement to establish a more sustainable quality assurance system.